A New Pleistocene Faunule from Meade County, Kansas - Claydon C. Couri (Hello World!, 1973)
A molluscan faunule of Kansan age, here named the Silage Pit faunule, containing 31 species, is reported from Meade County, Kansas. The stratigraphic sequence at the Silage Pit, and the geologic ranges of the assemblage suggest a Kansan age for the sediments from which the faunule was collected. The faunule, assigned to the Cudahy fauna, contains one species, Strobilops affinis (?) not previously reported from other Cudahy assemblages. The habitats inferred from the molluscan assemblage consist of a marsh, probably bordering a small pond, and surrounded by tall grass, brush, and scattered trees. The climate at the time the faunule lived was probably characterized by cooler summers than those of the present. Precipitation was probably more effective, due to less evapotranspiration, or greater in amount than at present.